Global library marketing research: A scientometric assessment of publications output during 2006–2017. Issue 3 (17th October 2018) - Gupta, Dinesh K.; Gupta, B.M.; Gupta, Ritu
Abstract : Purpose: The purpose of this paper is to quantitatively and qualitatively analyze library marketing research output using select bibliometric indicators with the aim of identifying top-performing countries, subject subthemes, organizations, authors and journals in the area. Design/methodology/approach: The present study has examined 520 publications in library marketing, as indexed in Scopus database during 2006–2017. The study has statistically assessed processed publications and citations data into tables in order to ascertain research growth rate trends, global publication output and share, citation impact and distribution of library marketing research by country of publication, international-level collaborating country share of publication, by broad subject areas and preferred media of research communication. The study also provides bibliometric profile of top research organizations and authors in terms of their publications and citation indicators. Findings: The body of literature in library marketing research is still very small, highly scattered and has so far registered no growth during the last 12 years, i.e. 2006–2017. Library marketing research is yet to emerge as a popular research area in library and information science. The USA dominates The library marketing research in the world, whereas other top participating countries including India, China, Japan, Canada, etc., are distant cousins. Top research institutions in the area of library marketing across the world include City University of New York, Florida State University, University of Texas at Austin, USA, Loughborough University and University of Sheffield, UK. The major focus of library marketing research was on academic libraries, followed by public libraries and medical libraries. Of late, the use of social media has emerged as an alternative to traditional library marketing techniques. Research limitations/implications: The scope of study describing the status of library marketing research is limited to the period 2006–2017. The results of the study should interest researchers in finding solutions to formulating future library strategies and programs for achieving sustainable growth in this area of study. Originality/value: The present study in library marketing research should be of interest to researchers in evolving, and formulating theories/best practices/and policies/programs for outreach to current and potential users for promoting library products and services.